Spanish teachers’ perceptions of motivations, opportunities, and barriers regarding Education for Sustainable Development: an exploratory study - Vergara-Arteaga, Marcela; Albareda-Tiana, Silvia; Graell-Martín, Mariona; Fuentes Loss, Mariana (Frontiers in Education, 2025)
IntroductionThis pilot study investigates teachers’ perceptions of motivations, opportunities, and barriers associated with Education for Sustainable Development (ESD) across different educational levels. Understanding these perceptions is essential for identifying factors that foster or hinder the integration of sustainability into educational practice.MethodsA quantitative design was employed using a validated self-completion online questionnaire distributed to a non-probability sample of 150 teachers in Spain. All participants had prior experience in ESD and voluntarily provided written informed consent.ResultsThe findings indicate that transcendent motivations, particularly the desire to contribute to the common good, are the most significant drivers. Institutional cooperation and the integration of sustainability into the strategic planning of educational institutions are perceived as key opportunities. Conversely, barriers such as consumerism and the need for specialized ESD training were identified. Strong positive correlations emerged between intrinsic and transcendent motivations and perceived opportunities for ESD.DiscussionThese results highlight the importance of reinforcing motivations and institutional opportunities to foster sustainable behaviors in educational settings. As one of the few quantitative studies examining teachers’ perceptions of ESD across all educational levels, this research provides a valuable foundation for informing future teacher education programs and public policy initiatives in sustainability education.